Zoe Saldana or Zoë Saldaña?: cinematic dominicanidad and the Hollywood star. Issue 1 (2nd January 2017) - Goin, Keara K.
ABSTRACT: This article investigates Dominican cinematic celebrity through the eyes of the Dominican community based on the findings from my New York City ethnographic fieldwork. Investigating the ways in which audiences interpret actress Zoe Saldana in roles and her star text, my research focused on star–audience relationships and the role of such relationships in the articulation of a Dominican-American identity. Furthermore, this article frames audience responses to Saldana in terms of Dominican authenticity, cultural trust, and the post-racial raced body. Building on star/celebrity studies scholarship alongside scholarship rooted in critical race theory, I contend that Saldana is perceived as sacrificing potential Dominican-American identification and fandom in exchange for mainstream Hollywood success. By self-fashioning her star text as a moving target, Saldana has created role flexibility while simultaneously serving as a synecdoche of the mediated invisibility of dominicanidad .